FORMULATION AND CHARACTERIZATION OF IONIC LIQUID IN OIL MICROEMULSIONS - SINGH, DILRAJDEEP (IRC, 2017)
Recently there have been various breakthroughs in the development of new types of drugs and drug delivery methods. Transdermal drug delivery (TDD) provides a safe and non-invasive method of drug delivery. TDD is yet to reach its full potential due to the poor solubility of many drugs in pharmaceutically accepted solvents. Ionic Liquids (ILs) are known to solubilize that have poor solubility but its application for TDD is limited by the hydrophobic barriers of the skin. This limitation can be overcome by incorporating hydrophobic domains in the IL containing solution by the formation of microemulsions (MEs). This research focusses on the formulation of such MEs by using pharmaceutically accepted components. The IL used in this study is 1-ethyl-3-methylimidazolium acetate. Taguchi’s experimental design was used to identify the effects surfactant ratio, surfactant concentration, IL content and temperature towards droplet size and drug solubility. In this approach, nine MEs were formed with varied parameters based on Taguchi’s design and ACV was dissolved in these MEs. All the MEs used IPM as the continuous phase and a surfactant blend of Tween-80 and Span-20 was used. It was seen that as surfactant ratio increases (increasing Tween-80), both the droplet size and drug solubility increases. It was also seen that as the surfactant concentration increases there is an increase in drug solubility but there is a decrease in particle size. As IL content and temperature increases there was an increase in both drug solubility and droplet size. The parameter that influences droplet size the most is surfactant ratio whereas the parameter that influences the drug solubility the most is IL content. The parameters were further optimized to identify the conditions that will give the highest drug solubility and lowest droplet size. It was concluded that the optimized conditions can be achieved by using surfactant ratio as 2:3, surfactant concentration as 25wt%, ionic liquid content at 2wt% and temperature at 30°C.